Fractional Delay Time Embedding of EEG Signals into High Dimensional Phase Space - Damasevicius, R.; Martisius, I.; Jusas, V.; Birvinskas, D. (Elektronika ir Elektrotechnika, 2014)
We propose a method for reconstruction of the high-dimensional phase space of the electroencephalography (EEG) signal. The method is based on the selection of positive trajectories from the phase space, distance-adaptive sampling of the negative trajectories from the phase space, classification of trajectories in the phase space, and reconstruction of a fuzzy state of the signal for classification of EEG signals. DOI: http://dx.doi.org/10.5755/j01.eee.20.8.8441